Making Use of UNIX* - Budgen D; Edward Arnold (1985)
The UNIX system is introduced through a gradual logical progression. Preface, Introduction, Where to Begin, Getting Started, A Bit About Files, Test Editing, Building Programs, Running Programs with the UNIX Shell, UNIX Under Another Name, Developing and Maintaining Programs with UNIX, Text Handling on UNIX and the Roff Programs, Management and Communication on the UNIX System, A Few More Software Tools, More About Files and a Bit About Devices too, Processes on UNIX, Device Driver Processes, Special Characters, Index.